THE ROLE OF ADENOSINE MONOPHOSPHATE-ACTIVATED PROTEIN KINASE AND HIGH-MOBILITY GROUP BOX 1 PROTEIN IN EARLY DIAGNOSIS OF NEONATAL SEPSIS - Orujova, P.A.; Sultanova, N.H. (World of Medicine and Biology, 2024)
Neonatal sepsis, a significant cause of infant mortality, necessitates early diagnosis for effective intervention. Current diagnostic markers, such as C-reactive protein and procalcitonin, exhibit limited sensitivity and specificity. This study investigates the potential of adenosine monophosphate-activated protein kinase and high-mobility group box1 protein levels as early diagnostic biomarkers for neonatal sepsis. We examined 143 neonates with suspected sepsis, analyzing clinical and laboratory data, including complete blood cell count, C-reactive protein, procalcitonin, fibrinogen, lactate, HCO3, and base excess levels, alongside adenosine monophosphate-activated protein kinase and high-mobility group box1 protein levels using enzyme-linked immunosorbent assay. Our findings indicate elevated adenosine monophosphate-activated protein kinase and high-mobility group box 1 levels in septic neonates compared to non-septic counterparts, with significant correlations between these markers and disease severity. These results suggest that adenosine monophosphate-activated protein kinase and high-mobility group box1 could serve as reliable biomarkers for early sepsis detection, potentially guiding timely and appropriate therapeutic interventions. Further research is recommended to validate these biomarkers' clinical utility in neonatal sepsis diagnosis.
Keywords: adenosine monophosphate-activated protein kinase; high-mobility group box1; neonate; sepsis